Residents' pro-tourism behaviour in a time of COVID-19. Issue 8 (23rd May 2022) - Woosnam, Kyle Maurice; Russell, Zachary; Ribeiro, Manuel Alector; Denley, Tara J.; Rojas, Camila; Hadjidakis, Erin; Barr, Joseph; Mower, Jackson
Abstract: Given the expediency with which some U.S. governors have reopened their states to tourists, this research focuses on residents' responses to pro-tourism behaviour within the State of Georgia—one such state where contentious perspectives have been voiced. This work tests a social exchange model which includes four potential predictors of residents' pro-tourism behaviour. Eight of the 11 proposed model hypotheses were supported. Though perceived risk of COVID-19 was not a significant predictor, perceived positive and negative tourism impacts were the strongest. Local and state destination marketing organizations will be best served in applying our findings in efforts to continually monitor residents' perspectives as more individuals receive the COVID-19 vaccination.